Participatory video as a tool for co-management in coastal communities: a case study from Madagascar - Carter, Amber Lucy; Maniry Soa, Symphorien Nihala; Arnull, Jessica; Antion, Paul; Tudhope, Alexander W.; Wilson, A. Meriwether W. (Frontiers in Human Dynamics, 2023)
Here we examine participatory video (supporting a group to make a film around a specific issue) as a tool to facilitate input of local knowledge and empower communities in stewardship over their local marine resources. We draw from the "Voices of the Vezo" project, where researchers collaborated with a co-management partner organization and local youth to create participatory videos in traditional Vezo fishing communities in southwest Madagascar. The project focused on documenting and sharing local knowledge on shifting social-ecological conditions. Four communities participated in the project with 90 people interviewed and seven short films (7-15 minutes) created. The films were shared in the communities at public cinema nights and made widely available online. This paper describes the Voices of the Vezo project's process and outputs, examines participatory video's potential as a tool for community co-management, and outlines practical challenges and recommendations for implementing a participatory video project. We found videography to be a powerful tool for synthesizing local knowledge of shifting social and ecological conditions, especially where written records are scarce. We also identified specific examples where gathering and sharing community perceptions of marine ecosystem decline could foster discussion and action towards locally driven management interventions. Youth participants in the Voices of the Vezo project reported gaining knowledge and motivation to address marine management issues, indicating the potential for participatory video processes to cultivate local leadership. Finally, for participatory video practitioners, we found important practical considerations to help minimize biases when supporting communities with a participatory video process.